Application Of Organizational Culture In Improving The Performance Of The State Civil Apparatus In Pekanbaru City - Raharjanto, Tri (International Journal of Demos (IJD), 2022)
AbstractThe government is obliged to provide good public services for its people, but the low performance of the apparatus and the still complicated bureaucracy causes public services to be not optimal and it is not uncommon to receive complaints from the public. It happened in the city government of Pekanbaru as well. To effectively serve the public, it is necessary to cultivate the right mindset and attitude. This study's goal is to shed light on how organizational culture can be leveraged to boost the efficiency of Pekanbaru's government institutions. This study takes a descriptive, qualitative approach to presenting its findings. According to the findings, the performance issues of Civil Servants will be implemented and fulfilled if the organization maintains its organizational culture. Maintaining a positive climate is one way in which organizational culture can boost performance, so a high level of performance can be expected when the culture is strong. Conversely, a low level of performance can be expected when the culture is weak.Keywords: Organizational Culture, State Civil Apparatus, Public Service.